Factors effective on students’ leaving health education groups for tobacco use prevention on virtual networks: A qualitative study: Students’ leaving the groups of health education - Khayyati, Fariba; Ebtekar, Fariba; Amjadian, Mohiadin; Fallahi, Arezoo (Chronic Diseases Journal, 2023)
BACKGROUND: This study was conducted with the aim to answer the following questions: What were the main reasons for students’ leaving the Telegram network group? How could they be encouraged to stay in such groups? METHODS: This was a qualitative study based on ‎ the content analysis method of Hsieh and Shannon. Using purposive sampling method, 24 students were recruited from the Islamic Azad University of Saqez in Iran in 2020. Nvivo software was used for data analysis. The reliability of the findings was insured through transcribing the data as soon as possible, accurate recording of the steps of the study, and using a suitable data collection method. RESULTS: The codes were placed into 10 subcategories and 3 main categories including the challenges of staying in the channel, smoking and not intending to quit, and motivational factors affecting the staying of individuals in the group. CONCLUSION: Most of the participants reported the low attractiveness of the channel, the cost of the Internet, Telegram filtering, and cultural reasons as significant challenges. Using photos instead of texts, posing questions for group members to answer, putting story series on the channel, advertising on other channels for this channel, and photos or GIFs were described as motivations for staying on the channel.